Land use planning conflicts with world heritage convention in Australia - Keane, Adrienne (2014)
Despite its international status as a world heritage area, Australia’s Great Barrier Reef (GBR) is under threat from development. Activities relating to primary resource extraction and increasing urbanization along the adjoining coastal lands not only threaten its status but illustrate the profound dilemma of development and the conservation of natural values. Criticisms of world heritage as a protective mechanism lie in the ambiguity in its operations particularly as there are no direct controls over the signatories (Evans, 2002) with the only leverage to exact compliance being the delisting or threat of delisting a property (Hazen, 2008; Maswood, 2000). Commentary suggests a lack of connection between the international intent of world heritage and the operationalization of it into national and local management regimes (Fowler, 2007; Lennon, 2006; Pendlebury, Short and While, 2009). Under the UNESCO consideration to put the GBR on the “in-danger” list, Australia has embarked on revising its development assessment process. This paper examines the newly devised strategic environmental assessment. While UNESCO is complementary to Australia’s policy shift, it remains watchful over the management of the GBR and the port development that threatens its integrity. This paper outlines the planning frameworks and Australia’s response to UNESCO, concluding that proactive measures have been taken but there is conflicting evidence to demonstrate that these will not protect an internationally important place from development.